2019
DOI: 10.1097/mnh.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-based contrast agents

Abstract: Purpose of review The hegemony of gadolinium-based contrast agent-induced adverse events stretches beyond those who have renal impairment. ‘Nephrogenic’ systemic fibrosis is a misnomer: gadolinium-based contrast agents are the known trigger for the disease; kidney impairment is a risk factor. Impaired (true) glomerular filtration may be one catalyst for gadolinium-based contrast agent-induced adverse events, but it is increasingly evident that the same cluster of symptoms occurs in patients with normal renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“… [129] CMR contrast dye (i.e., gadolinium) should be use with caution in patients with severe kidney insufficiency, as this may increase the risk of nephrogenic systemic fibrosis. [130] CMR nephrogenic systemic fibrosis can occur months after exposure and may be manifest by erythematous and edematous skin plaques mainly to the extremities, joint contractures, and respiratory failure. Beyond renal dysfunction, other risk factors for gadolinium-based contrast nephrogenic systemic fibrosis include proinflammatory state (e.g., major surgery, infection, malignancy), thrombotic events, and high-dose erythropoietin dose.…”
Section: Imaging Studiesmentioning
confidence: 99%
“… [129] CMR contrast dye (i.e., gadolinium) should be use with caution in patients with severe kidney insufficiency, as this may increase the risk of nephrogenic systemic fibrosis. [130] CMR nephrogenic systemic fibrosis can occur months after exposure and may be manifest by erythematous and edematous skin plaques mainly to the extremities, joint contractures, and respiratory failure. Beyond renal dysfunction, other risk factors for gadolinium-based contrast nephrogenic systemic fibrosis include proinflammatory state (e.g., major surgery, infection, malignancy), thrombotic events, and high-dose erythropoietin dose.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…The current Gd chelate-based MRI for stroke has relatively low sensitivity and can cause side effects, such as nephrogenic systemic fibrosis and intracranial gadolinium deposition [ 70 , 107 , 108 , 109 , 110 ]. Therefore, it is urgent to promote new and safer research imaging methods for the diagnosis and analysis of stroke.…”
Section: The Imaging Applications Of Inorganic Nanomaterials In Different Brain Disease Modelsmentioning
confidence: 99%
“…86,87 In the past years, it was shown that persons with normal renal function can also develop NSF when exposed to GBCA, but until the exact pathophysiology of GBCA-induced disease is better understood, alternative gadolinium-free methods should be used whenever possible in advanced CKD. 87,88 Native T1 is a novel noncontrast CMR technique based on the longitudinal recovery time of hydrogen atoms following their excitation. In any given magnetic field strength, every tissue will produce a specific range of values.…”
Section: Ard Iac Mag Ne Ti C Re Sonan Ce (Cmr )mentioning
confidence: 99%
“…In advanced CKD, the usage of gadolinium based contrast agents (GBCA) should be considered individually as it is limited by the risk (<1%) of developing a potentially lethal condition, nephrogenic systemic fibrosis (NSF) . In the past years, it was shown that persons with normal renal function can also develop NSF when exposed to GBCA, but until the exact pathophysiology of GBCA‐induced disease is better understood, alternative gadolinium‐free methods should be used whenever possible in advanced CKD …”
Section: Cardiac Magnetic Resonance (Cmr)mentioning
confidence: 99%